THE INFLUENCE OF INVESTMENT KNOWLEDGE, RISK TOLERANCE, AND INVESTMENT EXPERIENCE ON INVESTMENT DECISIONS WITH TECHNOLOGICAL ADVANCEMENT AS A MODERATING VARIABLE - Elly Karlina; Erna Listyaningsih; Harold Kevin Alfredo (International Journal of Management, Economic and Accounting, 2026)
This study examines the influence of investment knowledge, risk tolerance, and investment experience on investment decisions, with technological advancement as a moderating variable. The rapid growth of capital market participation in Indonesia, particularly among university students, highlights the increasing interest in investment activities. However, this growth is not always accompanied by high-quality decision-making, as many investors tend to rely on trends and emotional responses rather than rational evaluation. This research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to students, and the analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA). The findings reveal that investment knowledge and risk tolerance have a positive and significant influence on investment decisions, while investment experience does not have a significant effect. Furthermore, the results indicate that technological advancement does not significantly moderate the relationship between investment knowledge, risk tolerance, and investment experience on investment decisions. These findings emphasize the importance of financial literacy and individual risk preferences in improving investment decision-making quality. The study also suggests that technological advancement functions more as a supporting factor in investment activities rather than as a moderating factor influencing the relationships among the studied variables.